The World Bank, Improving the Quality of Governance in a Changing World, the Situation of Poland, and the Challenges of the Economic Crisis - Rutkowski, Michał (Journal of Public Governance, 2009)
It’s in the early 1990s that the World Bank first introduced the term “good governance” in its documents and aid programs. After the reorganization of 1997, a new public governance sector was formed in the Bank and a list of six indicators of good governance was compiled. The indicators were subsequently used in the research on the quality of governance in Poland, and the results clearly showed that the country scored low in all aspects of good governance, notably in public sector transparency, quality of regulation, law enforcement, as well as efficiency and effectiveness of carrying out public duties by the administration. The world economic crisis emphasized the role of good governance and highlighted its shortcomings, especially in the area of the economy of attention, where neglecting subprime mortgages and relations between interest rates and mortgage lending led to a disastrous chain effect. The crisis made evident the low quality of governance (both at the level of the state and the organization) and emphasized the need for flexible adjustments to ever changing circumstances (ability to shift attention) and the potential positive role of the matrix structure at the organization level. In fact, a need to move from linearity and unequivocal relations to flexibility and ability to modify appears to be among the main lessons of the crisis. The World Bank tries to make use of this lesson in its cooperation with governments and international organizations, never falsely assuming it is more competent in fighting corruption.